Concentración de nitritos polifosfatos y aglutinantes en chorizos comercializados en la ciudad de Riobamba-Ecuador - Cárdenas Gaspata, Alan Joel (2025)
In the city of Riobamba, most studies on food safety have primarily focused on the microbial load of food products, leaving a significant gap in the available informa t ion regarding their physicochemical analysis. This gap is particularly evident in the processed meat industry, such as chorizos, where additives enhance preservation, flavor, and texture. Among these products' most common and relevant additives are sodium nitrite, polyphosphates, and binders such as starch. While these substances benefit specific product attributes, they require strict control to ensure they remain within permitted limits and do not pose a risk to consumer health. Therefore, this observational and descriptive study aimed to analyze the concentration of sodium nitrite, polyphosphates, and binders in 15 chorizos brands sold in Riobamba, Ecuador. It was essential to use specific methods and recognized to conduct the analysis. Sodium nitrite was quantified using the spectrophotometric method in compliance with INEN 784 regulations; it was possible to determine polyphosphate concentration following the AOAC 995 methodology. The researcher performed the Starch detection using the acid hydrolysis method based on the Mexican standard F321-S 1978. The results revealed that all analyzed brands complied with the permitted limits for sodium nitrite and polyphosphates, demonstrating adequate control of these additives in chorizo production. However, in the starch analysis, 8 out of the 15 brands tested positive with the Lugol test, which detects the presence of starch. These brands exhibited high starch percentages, suggesting that while sodium nitrite and polyphosphate control is satisfactory, there is a need for greater oversight and regulat ion in the use of starch as a binder in chorizos. The study concludes that additional research is crucial for evaluating the presence and concentration of these additives in other food products and establishing specific minimum limits to ensure compliance with expected food quality and safety standards. It is advisable to implement stricter regulations and periodic controls to ensure the quality and safety of meat products regarding their chemical characteristics, thereby protecting consumer health.